(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of low-dose Thalidomide combined with Corticosteroids in patients with myelofibrosis at the National Institute of Hematology and Blood Transfusion. Methods: A case series descriptive study was conducted on 28 patients with myelofibrosis treated with low-dose Thalidomide combined with Corticosteroids during the period 1/2019-8/2025. Results: After 3 months of treatment, 71.4% of patients achieved Hb improvement, with a mean increase of 22.25 g/L, patients with baseline Hb ≥ 70 g/L had a seven-fold higher likelihood of Hb response compared with those with Hb < 70 g/L. The rates of improvement in thrombocytopenia and splenomegaly were 64.7% and 32.1%, respectively. After 3 months, patients continued treatment with Thalidomide monotherapy, and responses in anemia, thrombocytopenia, and splenomegaly were maintained at rates of 90%, 90.9%, and 57.1%, respectively. Regarding adverse events, leukocytosis and thrombocytosis were observed in 17.9% and 28.6% of patients, respectively, with grade 3 events accounting for 3.6% and 7.1%. The most common non-hematologic adverse event was constipation. Other adverse effects included sedation, paresthesia, hyperglycemia, infections, and thrombosis; however, each occurred in less than 30% of patients, and no grade 3 events or treatment discontinuations were reported. Conclusion: The treatment regimen of low-dose Thalidomide combined with Corticosteroids is effective in improving clinical manifestations, including anemia, thrombocytopenia, and splenomegaly, in patients with myelofibrosis, with acceptable adverse effects.